Pengembangan Bakat Dan Minat Mahasiswa Dalam Bidang Olahraga Melalui Pengenalan Dan Pendampingan Olahraga Panahan - Bramantha, Heldie; Setiawan, Gustilas Ade (Abdi Panca Marga, 2022)
Archery is a sport that is recommended in Islam and sunnah by the prophet Muhammad Shallalahu 'alaihi wasallam. This sport has long been known in Indonesia, by carrying out archery activities each individual is able to train strength, endurance, focus, hand and eye coordination, balance, increase hand and finger flexibility, increase patience and build self-confidence. The problem that occurs in the community in the city of Situbondo, especially for students at the Abdurachman Saleh University Situbondo, is that Archery is still not well known and is also still less attractive to the public because archery has not yet become a "free" sport of football, badminton, futsal, or basketball. Students also do not really know the sport of archery and what are the benefits of doing archery regularly. The lack of introduction to archery from sports coaches or agencies such as KONI related to archery is also a problem. The PKM activities carried out by the service team used the lecture, demonstration and practice methods, besides that, an archery competition simulation was also held. The result of this service is the increase in community knowledge and skills about archery, in addition to increasing knowledge of facilities and infrastructure will have an impact on increasing interest in sports, especially in the field of archery.